A Spectral-Analytic Test of the Long-Swing Hypothesis in Canada - Harkness, Jon P. (The Review of Economics and Statistics, 1968)
T HE recent development of spectral analysis as a tool for analyzing economic time series has provided a particularly neat method for independently testing the existence of Kuznets cycles. Researchers who have applied this technique, however, have produced mixed results. Adelman shows that such cycles do not exist in the United States data ' while Hatanaka and Howrey, in a criticism of Adelman's work, leave readers with, at best, an agnostic view.2 But both these studies have been poorly conceived with respect both to spectral analysis and to the particular version of the longswing hypothesis tested. The intention of this paper is to attempt to resolve the long-swing controversy, insofar as the Canadian data are concerned, by the application of spectral analysis to a large number of historical time series. For the purpose of comparison with results obtained in the United States this will initially mean applying what might be called the Adelman-Hatanaka-Howrey test. Finally, however, this test will be reformulated and reworked in a manner which is more compatible with spectral analysis and which makes more sense with respect to the long-swing hypothesis. Section II briefly describes and lists some important properties of spectral analysis while section III presents some of the practical considerations involved in applying this technique to the long-swing controversy. Section IV summarizes the results of the spectral estimates. Conclusions are in section V. IL